2020
DOI: 10.1590/fst.03919
|View full text |Cite
|
Sign up to set email alerts
|

Addition of green banana biomass as partial substitute for fat and encapsulated Lactobacillus acidophilus in requeijão cremoso processed cheese

Abstract: This study evaluated the effects of the addition of encapsulated Lactobacillus acidophilus and green banana biomass on the characteristics of requeijão cremoso processed cheese during the storage period of 45 days under refrigeration. The elaborated requeijões cremosos processed cheeses included addition of encapsulated Lactobacillus acidophilus as probiotic source, and green banana biomass as partial fat substitute, in a total of five treatments. Analyses were performed to evaluate probiotic viability, microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…Thus, the best choice for films would be those presenting moderate elasticity. Pivetta et al (2020) mentioned that higher percentage of starch result in lower elasticity. Specifically, amylose content in starch granules has a significant impact on the physicochemical, thermal and rheological properties (Ee et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the best choice for films would be those presenting moderate elasticity. Pivetta et al (2020) mentioned that higher percentage of starch result in lower elasticity. Specifically, amylose content in starch granules has a significant impact on the physicochemical, thermal and rheological properties (Ee et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, films used to protect foods with high water activity and those used to avoid exudation from fresh or frozen products, have distinct solubilities. Studying the addition of green banana biomass in a processed food, Pivetta et al (2020) concluded that it provided an increase in moisture and water activity due to its water retention capacity related to the high content of resistant starch.…”
Section: Methodsmentioning
confidence: 99%
“…Cheese is one of the best carriers for probiotics (Pivetta et al, 2020). The development of probiotic cheeses can be very strain-dependent as many of the probiotic strains showed insufficient performance in the cheese environment (Shori et al, 2018;Silva et al, 2018;Prezzi et al, 2020).…”
Section: In Cheesementioning
confidence: 99%
“…A low GI can help keep blood sugar levels stable, and has been associated with weight control and decreased risk of developing diabetes (Annison & Topping, 1994). Due to low cost and nutritional value of the green banana, many studies are utilized as a functional ingredient in various food products such as bread, snacks, pasta, cheese, and smoothie (Santos et al, 2018;Pivetta et al, 2020;Ribeiro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%